Definite intensity-modulated radiotherapy with concurrent chemotherapy more than 4 cycles improved survival for patients with locally-advanced or inoperable esophageal squamous cell carcinoma - Hsieh, He-Yuan; Hsu, Chung-Ping; Yeh, Hui-Ling; Chuang, Cheng-Yen; Lin, Jai-Fu; Chang, Chen-Fa (The Kaohsiung journal of medical sciences, 2018)
We investigated which prognostic factor could improve survival for esophageal cancer patients who received definite concurrent chemoradiation (CCRT). Eighty patients with age ≥18, Karnofsky Performance Scale (KPS) ≥ 60, and clinical stage T1-4N0-3M0 esophageal squamous cell carcinoma were enrolled from July 2004 to December 2015. They underwent definite intensity-modulated radiotherapy (IMRT) with or without simultaneous integrated boost to the primary tumor, and reception of concurrent chemotherapy ≥ 1 cycle. The primary endpoints were overall survival (OS), locoregional progression-free survival (LRPFS) and distant metastasis-free survival (DMFS). The median follow-up duration for alive patients was 21.5 months. The rates of 2-, 3- and 5-year OS/LRPFS/DMFS were 23.8%/53.5%/49.3%, 19.1%/44.6%/49.3%, and 13.0%/44.6%/43.9%, respectively. Only the non-clinical complete response (non-cCR) after CCRT was an independent poor prognostic factor in OS (HR 3.101, 95% CI 1.535–6.265, p = 0.0016). Radiation dose >50.4 Gy and chemotherapy ≥4 cycles significantly predicted better LRPFS (p = 0.0361 and 0.0163, respectively). Poorly differentiated tumor and stage III disease have poor DMFS (p = 0.0336 and 0.0411, respectively), and chemotherapy ≥ 4 cycles was a better predictor (p = 0.0004). In subgroup analysis, patients who received radiation dose ≤50.4 Gy with concurrent chemotherapy ≥4 cycles had the best survival outcome with 1-, 2-, 3- and 5-year survival rates of 73.7%, 39.4%, 31.5% and 17.5%, respectively. In conclusion, definite radiotherapy with concurrent chemotherapy ≥4 cycles improved the survival for patients with inoperable or locally-advanced esophageal squamous cell carcinoma.